2015
DOI: 10.1007/s10238-015-0365-2
|View full text |Cite
|
Sign up to set email alerts
|

Par3 regulates invasion of pancreatic cancer cells via interaction with Tiam1

Abstract: The conserved polarity complex, which comprises partitioning-defective proteins Par3, Par6, and the atypical protein kinase C, affects various cell-polarization events, including assembly of tight junctions. Control of tight junction assembly is closely related to invasion and migration potential. However, as the importance of conserved polarity complexes in regulating pancreatic cancer invasion and metastasis is unclear, we investigated their role and mechanism in pancreatic cancers. We first detect that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Silencing of the expression and/or function of these proteins, either due to genetic alterations or epigenetic regulation, modulates claudin expression, and induces loss of polarity and EMT [8, 22, 53]. Interestingly, genetic modulation of claudin proteins in mice or cancer cells can similarly affect these signaling cascades, suggesting a feedback regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of the expression and/or function of these proteins, either due to genetic alterations or epigenetic regulation, modulates claudin expression, and induces loss of polarity and EMT [8, 22, 53]. Interestingly, genetic modulation of claudin proteins in mice or cancer cells can similarly affect these signaling cascades, suggesting a feedback regulation.…”
Section: Introductionmentioning
confidence: 99%
“…F2rl2 is a member of the protease‐activated receptor‐3 family and is involved in homeostasis, adhesion, proliferation, and migration (Fig. 6) (46, 47). Although we observed that both genes were hypomethylated at this specific site, we noticed a 76‐fold difference in the extent of underexpression, with Iqgap2 >378‐ and F2rl2 >5‐fold underexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic tumor, glioblastoma, head and neck squamous cell carcinoma, and esophageal squamous cell carcinoma, PAR3 acts as tumor suppressor and is positively associated with overall survival rate of cancer patients. [3][4][5][6][7] However, in some other tumors, such as liver cancer, ovarian cancer, and renal clear cell carcinoma, PAR3 overexpression supports cancer cell proliferation and is associated with poor cancer prognosis. [8][9][10][11] All these evidences implicated the complex regulatory network of cell polarity and its interaction with oncogenic and tumor suppressor pathways.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Also, PAR3 controls tight junction assembly in pancreatic cells and absence of PAR3 is associated with poor prognosis of pancreatic cancer. 5 In addition, PAR3 reduction has also been frequently reported in esophageal squamous cell carcinoma, 6 head and neck squamous cell carcinoma, and primary glioblastoma tumors, 7 all of which suggest a tumor-suppressing function of PAR3. However, all the growing evidences implicated the oncogenic role of PAR3.…”
Section: Introductionmentioning
confidence: 98%